Computer science - Theory and applications : 7th International Computer Science Symposium in Russia, CSR 2012, Nizhny Novgorod, Russia, July 3-7, 2012. Proceedings - Hirsch, Edward A. (Lecture Notes in Computer Science, 2012)
This book constitutes the proceedings of the 7th International Computer Science Symposium in Russia, CSR 2012, held in Nizhny Novgorod in July 2012. The 28 full papers presented in this volume were carefully reviewed and selected from 66 submissions. CSR 2012 was one of the events of the Alan Turing Year 2012, the topics dealt with cover substantial parts of theoretical computer science and its appcliations.